PRAKTIK FIKIH KESEHARIAN MINORITAS MUSLIM DI BALI - rahman, fathor (Jurnal Studi Agama dan Masyarakat, 2020)
This paper explored a daily fiqh practice or, more precisely, the practice of Islam among Muslim minorities in Bali, which is transformed into an adaptable form of religious diversity promoting harmony. In the midst of the strong domination of Hindu custom and the acts of violence by few Muslims in Indonesia, the Balinese Muslim community strived to manifest Islamic teachings (fiqh) in daily life having tolerant and moderate. Through two problems such as; how is the religious adaptation pattern of minority Muslim communities in Bali? How do Muslim communities establish inter-religious harmony as a manifestation of their daily fiqh? This study attempted